EDUCAÇÃO MATEMÁTICA FINANCEIRA: UMA ABORDAGEM SOCIOECONÔMICA NO 2º ANO DO ENSINO MÉDIO POLITÉCNICO - Fernandes, Pâmela Franco (2016)
This study aimed to investigate whether the teaching of financial mathematics, contextualized the lives of students, contributes to the satisfaction of learning and critical formation of this. Therefore, it was important to set some specific goals: 1) Make a survey on the socio-economic reality of the students, whose data will be used in the adaptation of problems involving financial mathematics education; 2) Check how students live consumerism and fashion in order to create environments discussion on the proposed mathematical problems. Research has qualitative character and was conducted with 24 students of 2nd year of high school at the State Education School Joaquim Nabuco. Initially it applied a socioeconomic questionnaire in order to adapt the activities and to support the proposed discussions during class. To facilitate the search, we use some proposed steps in Troubleshooting methodology and used as theoretical support the Critical Mathematics Education. The survey, conducted at the Polytechnic High School occurred during school math through activities involving percent, simple interest, compound interest, being prioritized moments of discussions about consumerism and its consequences. Seeking to meet the proposal of the Polytechnic, three students in this class conducted a survey in the Integrated Seminar, which aimed to investigate financial education in the municipality of Tupanciretã. Both the proposed activities in the classroom and the research carried out by students in the Integrated Seminar enabled the same deep critical analysis of the liquidity of human relationships present in society which is currently being built. The criticality, another focal point of the research was explored throughout the project, it is believed that this gave the students moments of full ownership, where everyone could express their opinions and thoughts. As well as awareness for the rejection of consumerism imposed by the current society, was worked every development of a new activity, with the aim, even more value to what had already been observed by the written questionnaire. As a product of this research, a learning object was built, covering the activities proposed in class in order to seek further attract the attention of young students for the socio-economic issues present in society.